Boundary objects in clinical simulation and design of eHealth. (June 2016) - Jensen, Sanne; Kushniruk, Andre
Development and implementation of eHealth is challenging due to the complexity of clinical work practices and organizations. Standardizing work processes and documentation procedures is one way of coping with these challenges, and acceptance of these initiatives and acceptance of the clinical information system are vital for success. Clinical simulation may be used as "boundary objects" and help transferring of knowledge between groups of stakeholders and help to better understand needs and requirements in other parts of the organization. This article presents a case study about design of electronic documentation templates for nurses' initial patient assessment, where clinical simulation was used as a boundary object and thereby achieved mutual clinical agreement on the content. Results showed that meetings prior to and in between workshops allowed all communities of practice an opportunity to voice their point of view and affect the final result. Implications of considering clinical simulations as boundary objects are discussed.